The Utilization Of Hard Waste As Percussion Learning Media In The Performing Arts Education Study Program Sultan Ageng Tirtayasa University (Universitas Negeri Semarang, 2022)
This study aims to develop learning media by using hard waste as a percussion instrument. The use of learning media at the university level is very important in the learning process. Learning media is useful as a tool for students to go through the teaching and learning process of percussion courses. This study uses qualitative analysis methods. Qualitative analysis research method is a research method used to collect, sort, classify, synthesize, make an overview, and create an index. The target of this research is the use of hard waste as a percussion learning medium in the Department of Performing Arts Education, Sultan Ageng Tirtayasa University. This research was carried out on the basis of environmental awareness which was applied by recycling hard waste into percussion instruments. Percussion using hard waste or what can be called Thrash Percussion, is an interesting and all-encompassing form of percussion that has been designed with the hope that anything that is no longer useful can still be used as a recycled musical instrument